Rhodochlanis suaedicola sp. nov. (Hemiptera: Sternorrhyncha: Psylloidea: Aphalaridae) associated with Suaeda japonica (Amaranthaceae) from Korea - Cho, Geonho; Burckhardt, Daniel; Lee, Seunghwan (Zootaxa, 2015)
A new psyllid species, Rhodochlanis suaedicola sp. nov., is described and illustrated from Korea based on adults and fifth instar immatures. Rhodochlanis is reported for the first time from Korea. The new species is associated with Suaeda japonica (Amaranthaceae) growing in saline habitats. Salt marshes in Korea are threatened by sea side developments. It is suggested that these habitats should be protected to ensure the survival of R. suaedicola.